THE EDUCATION FUNCTION OF EFFECTIVENESS ON LEADERSHIP BEHAVIOR, SCHOOL CLIMATE, AND TEACHER PERFORMANCE - Delita Pristyowati; Sri Rahayu; Wahidmurni Wahidmurni; Achmad Sani Supriyanto (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2021)
The cause of the decrease quality of education is the problem of school effectiveness. This study examines the variable model of school effectiveness on leadership behavior, school environment climate, and teacher performance. The research approach uses quantitative and correlational types. The population of this research is the teachers of Madrasah Ibtidaiyah Negeri in Malang City. The sampling technique is a saturated sample or census. The data collection tool is a questionnaire. Questionnaire statements assess on a Likert scale. Validity compares with calculated r-value with r table for Degree of Freedom (df) = n-k at Alpha 0.05. The reliability test carries with using the Cronbach Alpha test. Data analysis uses Partial Least Square (PLS) to analyze Outer Model and Inner Model data along with Bootstrapping. In the research findings, leadership behavior has a significant effect on teacher performance, and school climate has no impact on teacher performance. Principal leadership behavior and teacher performance affect the effectiveness of madrasas. Another finding is that an indirect effect between leadership behavior through teacher performance. There is no direct influence between school climate through teacher performance. School effectiveness is determined by teacher performance.